En contra de la ratificación judicial: el caso peruano - Villanueva, Rocío (Pontificia Universidad Católica del Perú, 2025)
This article proposes that judicial performance revalidation be eliminated from the Peruvian Constitution because it violates the principle of judicial independence and an individual’s right to be judged according to the law. The author sustains that it is a problematic and unreasonable institution. In the article, the jurisprudence of the Constitutional Tribunal is reviewed, since over the course of more than twenty years it has varied with respect to the legal nature of the judicial performance revalidation process, the rights of magistrates subjected to that process and the legal consequences in the judicial career of the decision against judicial performance revalidation. The article also contains a review of the jurisprudence of the Inter-American Court of Human Rights on judicial independence, emphasizing that the principle tries to control the reasons based on which judges decide cases. Additionally, it presents the judicial performance revalidation procedure, especially in relation to the aspects being evaluated, to the documentation asked of judges and to some of the criteria used in the evaluation. It also contains judicial revalidation figures for the 2001-2021 period and analyzes whether judicial performance revalidation fulfills its constitutional purposes or, on the contrary, is unreasonable and contributes to judges making decisions for the wrong reasons.

Este artículo plantea que la ratificación judicial sea eliminada de la Constitución peruana porque viola el principio de independencia judicial y el derecho de las personas a ser juzgadas desde el derecho. La autora sostiene que es una institución problemática e irrazonable. En el artículo se revisa la jurisprudencia del Tribunal Constitucional, pues a lo largo de más de veinte años ha ido variando en cuanto a la naturaleza jurídica de la ratificación judicial, a los derechos de los magistrados sometidos al procedimiento de ratificación y a las consecuencias jurídicas en la carrera judicial de la decisión de no ratificación. El artículo también contiene una revisión de la jurisprudencia de la Corte Interamericana de Derechos Humanos sobre la independencia judicial, poniendo especial énfasis en que tal principio trata de controlar los motivos por los que los jueces resuelven los casos. Asimismo, presenta el procedimiento de ratificación, especialmente en lo relativo a los aspectos que se evalúan, a la documentación que se solicita a los jueces y a algunos de los criterios que se utilizan en la evaluación. También contiene cifras sobre la ratificación en el periodo 2001-2021 y analiza si cumple sus fines constitucionales o si, por el contrario, es irrazonable y contribuye a que los jueces resuelvan por los motivos incorrectos.
Against Judicial Performance Revalidation: The Peruvian Case
Keywords: Judicial ratification; Independence of the judiciary; Justifying reasons; Explanatory reasons; Reasonability; Ratificación judicial; Independencia judicial; Razones justificativas; Razones explicativas; Razonabilidad; https://purl.org/pe-repo/ocde/ford#5.05.01